A Fatal Case of CO2 Intoxication in a Fermentation Tank. Issue 2 (14th January 2013) - Kettner, Mattias; Ramsthaler, Frank; Juhnke, Christian; Bux, Roman; Schmidt, Peter
Abstract: Carbon dioxide (CO2 ) is an odorless constituent of air. Higher concentrations can be detected in geothermal and automotive emissions, fermentation, and sublimation of dry ice. An unskilled worker entered a fermentation tank to clean it, which had not been done for about 5 months allowing for high concentrations of CO2 to build up. A second worker entered the tank to rescue the first one. Shortly after both were found the first worker was rescued directly whereas the tank had to be rotated to pull the second worker out. Cardiopulmonary resuscitation was successful only for the first worker. Medico‐legal autopsy showed bruises, hematoma, myocardial hemorrhage, and edema of the lungs. The right lung was vacuum degassed in an argon atmosphere and quadrupole‐mass‐spectrometry showed an elevated CO2 content in lung gases. Thus, CO2 intoxication/asphyxia in a vitiated atmosphere due to fermentation of wine mash was established as the cause of death.